Storying Equality: Narrative-Based Critical Literacy in Online English Language Teaching as a Transformative Space for Gender Justice and Social Inclusion - Gusti Nur Hafifah; Sofi Yunianti; Ari Setyorini (International Journal of Educational Narratives, 2026)
Background. The low literacy skills among Indonesia students is the main problem. Purpose. Therefore, this study aims to analyze the digital materials that foster critical thinking while addressing social issues, such as social inclusion and gender equality and the research questions focus on the module’s feasibility, the integration of critical literacy and GESI (Gender Equality and Social Inclusion) strategies, and the module’s suitability from user perspectives. Method. Thus, it used ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) which guided the development process over eight months, involving five experts, three model teachers, and six classes with 180 junior high school students. Results. The research findings indicate that expert validation, teacher evaluation, and student readability assessments confirmed the Si-Moli module as a valid and feasible tool for promoting critical literacy and Gender Equality and Social Inclusion (GESI) in English language learning. Quantitative evaluation results showed that the module received a high level of acceptance from experts, teachers, and students, with an overall mean score of 4.62 out of 5 (92.4%), indicating that it was perceived as highly relevant, practical, and effective. Conclusion. The module received positive feedback from experts, teachers, and students, who highlighted its potential to engage learners with important social issues while enhancing their language skills. However, improvements in website functionality, accessibility, language simplicity, and visual design were recommended to further enhance its usability and effectiveness.